Antibacterial and Antibiofilm Activities of Cinnamomum Sp. Essential Oil and Cinnamaldehyde: Antimicrobial Activities - Diego F. Firmino; Theodora T. A. Cavalcante; Geovany A. Gomes; Nairley C. S. Firmino; Lucas D. Rosa; Mário G. de Carvalho; Francisco E. A. Catunda Jr (The Scientific World Journal)
To assess the activities of essential oils derived from the trunk bark of Cinnamomum zeylanicum (EOCz) and Cinnamomum cassia (EOCc) as well as cinnamaldehyde on bacterial biofilms of clinical interest. Antimicrobial activity was assessed by the broth microdilution method to determine minimum inhibitory concentrations (MICs). Antibiofilm activity was assessed by quantifying the biomass and determining the number of viable cells. The chemical composition of the essential oils was determined. The results showed that the major component of EOCz and EOCc was cinnamaldehyde. For the assayed substances, biofilm biomasses were reduced by up to 99.9%, and Streptococcus pyogenes, Pseudomonas aeruginosa, and Escherichia coli biofilms were sensitive to all of the concentrations and substances analysed. In cell viability tests, 2 mg/ml of cinnamaldehyde reduced the number of viable cells by 5.74 Log CFU/ml. EOCz, EOCc, and cinnamaldehyde exhibited antimicrobial and antibiofilm activities. This work describes substances with potential use against infections caused by bacterial biofilms.